Edukasi Isi Piringku sebagai Upaya Meningkatkan Pemahaman Gizi Seimbang pada Siswa MI Nurul Huda di Dusun Slempit - Galuh Amelia Ragil Rahmanda (Nanggroe: Jurnal Pengabdian Cendikia, 2026)
The low level of understanding among elementary school students regarding balanced nutrition is one of the factors that can influence children’s eating patterns and health status. This study aims to improve students’ understanding of the concept of balanced nutrition through Isi Piringku education for students of MI Nurul Huda in Dusun Slempit. The activity was carried out through several stages: initial observation to determine the students’ level of understanding, implementation of education using interactive lecture methods and visual media, educational games (coloring, cutting, and pasting Isi Piringku pictures), and evaluation to measure the improvement in students’ understanding. The results showed that prior to the education session, most students did not understand the composition of Isi Piringku and the importance of consuming vegetables and fruits in their daily diet. After the educational intervention, there was an improvement in understanding, as reflected in the students’ ability to re-explain the concept of Isi Piringku, answer questions more accurately, and demonstrate awareness of the importance of consuming balanced nutritious foods.